Altered duodenal bile salt concentration and receptor expression in functional dyspepsia. Issue 9 (1st November 2018) - Beeckmans, Dorien; Riethorst, Danny; Augustijns, Patrick; Vanuytsel, Tim; Farré, Ricard; Tack, Jan; Vanheel, Hanne
Abstract : Background: Functional dyspepsia is a common functional gastrointestinal disorder in which a variety of pathophysiological mechanisms such as increased intestinal permeability and low‐grade inflammation are involved. The factor causing these alterations, however, has not been identified. Objective: We aimed to evaluate the luminal bile salt content and receptor expression in patients with functional dyspepsia and healthy volunteers. Methods: Gastroduodenoscopy was performed to obtain duodenal biopsies from 25 healthy volunteers and 25 patients with functional dyspepsia (Rome III) to measure duodenal bile salt receptor expression with Western blot. Duodenal fluid aspirates were collected at fixed time points during fasted and fed state conditions and bile salt composition analysis was performed by liquid chromatography‐mass spectrometry/mass spectrometry. Results: Patients ( N  = 17) displayed decreased fasted bile salt concentrations compared to healthy volunteers ( N  = 20) over time (1.8 ± 0.3 mM vs 3.6 ± 0.5 mM; p  = 0.03). In addition, an increased expression of duodenal bile salt sensor vitamin D receptor was found in patients (3.7 ± 1.0‐fold; p  < 0.0005; N  = 24 for both groups). Conclusion: Patients with functional dyspepsia are characterized by a decreased duodenal bile salt concentration in fasted state and an increased duodenal vitamin D receptor expression.